Pathogenic CD8+ T Cells Cause Increased Levels of VEGF-A in Experimental Malaria-Associated Acute Respiratory Distress Syndrome, but Therapeutic VEGFR Inhibition Is Not Effective - Pham, Thao-Thy; Verheijen, Melissa; Vandermosten, Leen; Deroost, Katrien; Knoops, Sofie; Van den Eynde, Kathleen; Boon, Louis; Janse, Chris J.; Opdenakker, Ghislain; Van den Steen, Philippe E. (Frontiers in Cellular and Infection Microbiology, 2017)
Malaria is a severe disease and kills over 400 000 people each year. Malarial complications are the main cause of death and include cerebral malaria and malaria-associated acute respiratory distress syndrome (MA-ARDS). Despite antimalarial treatment, lethality rates of MA-ARDS are still between 20 and 80%. Patients develop pulmonary edema with hemorrhages and leukocyte extravasation in the lungs. The vascular endothelial growth factor-A (VEGF-A) and the placental growth factor (PlGF) are vascular permeability factors and may be involved in the disruption of the alveolar-capillary membrane, leading to alveolar edema. We demonstrated increased pulmonary VEGF-A and PlGF levels in lungs of mice with experimental MA-ARDS. Depletion of pathogenic CD8+ T cells blocked pulmonary edema and abolished the increase of VEGF-A and PlGF. However, neutralization of VEGF receptor-2 (VEGFR-2) with the monoclonal antibody clone DC101 did not decrease pulmonary pathology. The broader spectrum receptor tyrosine kinase inhibitor sunitinib even increased lung pathology. These data suggest that the increase in alveolar VEGF-A and PlGF is not a cause but rather a consequence of the pulmonary pathology in experimental MA-ARDS and that therapeutic inhibition of VEGF receptors is not effective and even contra-indicated.